Method for realizing continuous degradation of pollutants under low dosage based on self-assembly induced carbon confinement material
By using self-assembly-induced carbon domain-limited materials in wastewater treatment to activate peracetic acid and generate advanced oxidative active species, the problem of high doses of catalytic materials and oxidant in the prior art is solved, and the low-cost continuous degradation effect of micropollutants is achieved.
Patent Information
- Application Number
- CN202411576251.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing advanced oxidation process based on peracetic acid has the problem of high dose of catalytic materials and oxidant addition in wastewater treatment, which leads to high engineering application costs and difficulty in achieving continuous degradation of micropollutants.
Using carbon domain-limited materials based on self-assembly induction, the continuous degradation of organic pollutants is achieved by activating peracetic acid at low doses to generate advanced oxidative active species such as hydroxyl radicals, organic radicals, singlet oxygen and Co(IV).
The efficient utilization of the oxidizing agent peracetic acid is achieved under the dosage of low-carbon limited-domain materials, which reduces the cost of wastewater treatment, and achieves the continuous degradation of micropollutants, and improves the recycling performance of catalytic materials.
Smart Images

Figure CN119503997A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and relates to a method for realizing continuous degradation of pollutants at a low dosage based on self-assembly induced carbon confined materials. Background Art
[0002] In recent years, risk prevention of new pollutants has received increasing attention. New pollutants have characteristics such as biological toxicity, environmental persistence, and bioaccumulation. Their environmental risks are hidden and difficult to control. Take naproxen, a new pollutant containing an aromatic ring structure, as an example. Naproxen is a typical non-steroidal anti-inflammatory drug and is widely used as an antibiotic worldwide. For this type of antibiotic micropollutants that contain aromatic ring structures, have poor water solubility, high fat solubility, and stable metabolism, water bodies are the main carriers of their distribution in the environment. Traditional methods such as adsorption, flocculation, and biological treatment are difficult to effectively remove such micropollutants. Compared with traditional treatment methods, advanced oxidation processes (AOPs) can achieve high-efficiency removal of antibiotics with little secondary pollution. They have been applied to the removal of difficult-to-degrade micropollutants and deep treatment of sewage.
[0003] Advanced oxidation processes based on peracetic acid (PAA-AOPs) have received widespread attention in recent years due to their high efficiency and environmental friendliness. Compared with traditional advanced oxidation processes, PAA-AOPs have a wider pH range of application. The oxidant peracetic acid (PAA) itself does not produce harmful byproducts and has both oxidation and sterilization functions. In existing reports, energy inputs such as ultraviolet light, ultrasound, sunlight and thermal energy, the addition of catalysts such as transition metal ions and their compounds, and non-metallic carbon materials can all achieve the cleavage of the OO bond of PAA, thereby activating PAA to produce hydroxyl (·OH), organic free radicals (RO·), singlet oxygen ( 1 O2) and high-valent metals, thereby effectively degrading micropollutants. Compared with the use of homogeneous catalytic materials to activate PAA, the use of heterogeneous catalytic materials to activate PAA can reduce the leaching of metal ions, thereby reducing secondary pollution, and can also achieve the recycling of catalytic materials.
[0004] Among the numerous catalytic materials used to activate PAA, cobalt-based heterogeneous catalytic materials have shown excellent performance in PAA activation. However, the limited effective activation sites of cobalt-based heterogeneous catalytic materials, the consumption of PAA by the water environment matrix, the occurrence of side reactions during the activation of PAA by cobalt-based catalytic materials, and the low activation efficiency have led to low utilization efficiency of PAA and catalytic materials in wastewater treatment. The resulting high cost problem is the biggest obstacle to the engineering application of this technology. At the same time, the actual treatment of wastewater is often a continuous and long-lasting process. How to achieve the continuous degradation of micropollutants in water bodies is also a key to reducing the cost of wastewater treatment. Therefore, if the efficiency of cobalt-based heterogeneous catalytic materials in activating PAA can be improved, the efficient utilization of PAA and the continuous degradation of micropollutants can be achieved at low dosages, it will have a positive significance for promoting the engineering application of PAA-AOPs. Summary of the invention
[0005] In view of the problems of high dosage of catalytic materials and peracetic acid and high engineering application cost in the existing advanced oxidation process based on peracetic acid, the present invention provides a method for achieving continuous degradation of pollutants at low dosage based on self-assembly induced carbon confined materials, so as to achieve efficient utilization of the oxidant peracetic acid at low dosage of carbon confined materials, mediate the continuous degradation of micropollutants, and reduce the treatment cost of wastewater containing organic pollutants.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] The method for achieving continuous degradation of pollutants at low dosage based on self-assembly induced carbon confined materials comprises the following steps:
[0008] Adding peracetic acid and a carbon-confined material to wastewater containing organic pollutants, treating the wastewater under stirring conditions, wherein during the wastewater treatment process, the carbon-confined material activates the peracetic acid to generate hydroxyl radicals, organic free radicals, singlet oxygen and Co(IV) to degrade the organic pollutants in the wastewater;
[0009] The carbon confined material is composed of a cobalt material and a nitrogen-doped carbon material coating the cobalt material, the cobalt material is composed of Co and CoO, and the carbon confined material is a nanoparticle with a core-shell structure.
[0010] In the above technical solution, the cobalt content in the carbon confined material is preferably 18wt% to 23wt%, and the nitrogen content is preferably 1.0wt% to 2.4wt%.
[0011] In the above technical solution, in the nitrogen-doped carbon material, the phase composition of carbon is graphitized carbon and disordered carbon, and the intensity ratio of the D band to the G band in the Raman spectrum of the nitrogen-doped carbon material is 0.98 to 1.85.
[0012] In the above technical solution, the functional groups contained in the nitrogen-doped carbon material include CH, CO, C=NC and NH.
[0013] In the above technical solution, the particle size of the carbon confinement material is preferably 10 to 20 nm.
[0014] In the above technical solution, the carbon confined material has a mesoporous structure with an average pore diameter not exceeding 10 nm.
[0015] In the above technical solution, the preferred method for preparing the carbon confined material is as follows:
[0016] (1) adding dopamine hydrochloride and a block copolymer to an ethanol-water solution, ultrasonically treating to form block copolymer-dopamine hydrochloride micelles, adding a water-soluble cobalt salt to the block copolymer-dopamine hydrochloride micelles, mixing thoroughly, adding 1,3,5-trimethylbenzene and ammonia water, stirring to react for 3 to 5 hours, separating the solid and the liquid, and washing the solid phase;
[0017] In this step, dopamine hydrochloride is added to the ethanol-water solution at a mass ratio of 1:(1.5-3) to the block copolymer, the concentration of dopamine hydrochloride in the ethanol-water solution is controlled to be 4-8 g / L, the concentration of the water-soluble cobalt salt in the block copolymer-dopamine hydrochloride micelle is controlled to be 2-4 mmol / L, and 1,3,5-trimethylbenzene and ammonia water are added at a volume ratio of (0.9-1.2):100 and (1-2):100 to the ethanol-water solution; the volume content of ethanol in the ethanol-water solution is 50%-60%;
[0018] (2) The solid phase obtained in step (1) is heated to 340-360° C. in a N2 atmosphere and kept at this temperature for 2-4 hours, and then heated to 800-900° C. and kept at this temperature for 1-3 hours.
[0019] Furthermore, in the above technical scheme, when preparing the carbon confined material, the preferred block copolymer is polyethylene oxide-block-polypropylene oxide-block-polyethylene oxide (PEO-PPO-PEO), for example, Pluronic F127 and P123, and the preferred block copolymer can also be polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol (PEG-PPG-PEG), for example, Pluronic F108 and F124.
[0020] In the above technical solution, when preparing the carbon confined material, the water-soluble cobalt salt may be cobalt nitrate, cobalt sulfate, or the like.
[0021] In the above technical solution, the dosage of peracetic acid in the wastewater is preferably controlled to be 50-400 μmol / L, and more preferably, the dosage of peracetic acid in the wastewater is controlled to be 50-200 μmol / L.
[0022] In the above technical solution, the dosage of the carbon confinement material in the wastewater is preferably controlled to be 5-50 mg / L, and more preferably, the dosage of the carbon confinement material in the wastewater is controlled to be 5-30 mg / L.
[0023] In the above technical scheme, the wastewater treatment time can be determined according to the specific water quality of the wastewater (such as the type and concentration of organic pollutants). Usually, the wastewater is treated until the removal rate of organic pollutants in the wastewater reaches a balance. Generally speaking, the wastewater treatment time is controlled to be 10 to 120 minutes.
[0024] In the above technical solution, during wastewater treatment, the temperature of the wastewater basically does not affect the degradation efficiency and effect of organic pollutants. In order to save wastewater treatment costs, wastewater treatment is usually carried out at room temperature, for example, the temperature of the wastewater can be controlled at 5 to 35°C.
[0025] In the above technical solution, during the wastewater treatment process, the stirring conditions are controlled to make the carbon confined material in the wastewater in a fluidized state.
[0026] In the above technical scheme, depending on the different block copolymers used in preparing the carbon confined material, the organic free radicals generated by activating peracetic acid in the prepared carbon confined material are CH3· and CH3COO·, or CH3COO· alone.
[0027] In the above technical scheme, the organic pollutants include but are not limited to phenol (PE), bisphenol A (BPA), sulfamethoxazole (SMX), sulfamethoxazole (SMZ), 4-chlorophenol (4-CP), ampicillin (AMP), naproxen (NAP) and sulfamethoxazole (SMX).
[0028] The present invention verifies through experiments that the carbon confined material has excellent recycling performance. In practical applications, it can be recycled to reduce wastewater treatment costs. Usually, the carbon confined material can be recycled 3 to 4 times.
[0029] The main reasons why the present invention can achieve efficient utilization of the oxidant peracetic acid at the dosage of low-carbon confined material are as follows:
[0030] The present invention confines Co@CoO nanoparticles in nitrogen-doped carbon materials through a self-assembly polymerization strategy to prepare carbon-confined materials. On the one hand, the coating of the nitrogen-doped carbon material shell can effectively reduce the leaching of metal ions and solve the problem of easy agglomeration and inactivation of metal nanoparticles. On the other hand, the Co@CoO nanoparticles are confined in the nitrogen-doped carbon material in the form of a core-shell structure, which can effectively adjust the electronic structure of the active site and achieve efficient catalytic activation of peracetic acid through the electronic synergy between Co and CoO. The nano-confinement effect of the nitrogen-doped carbon material can achieve the chemical conversion rate and selectivity of pollutants under milder conditions by enriching reactants, stabilizing transition states, changing the inner surface adsorption potential and redox state, thereby improving the utilization efficiency of oxidants, carbon-confined materials and active species.
[0031] Compared with the prior art, the technical solution provided by the present invention produces the following beneficial technical effects:
[0032] 1. The present invention provides a method for achieving continuous degradation of pollutants at low dosages based on self-assembly induced carbon-confined materials, the method is based on carbon-confined materials activating peracetic acid to produce advanced oxidation active species, and achieves efficient degradation of organic pollutants, the carbon-confined material is composed of a cobalt material and a nitrogen-doped carbon material coated with a cobalt material, the cobalt material is composed of Co and CoO, and the carbon-confined material is a nanoparticle with a core-shell structure. Due to the increase in the activity of the carbon-confined material, the method of the present invention can achieve a higher oxidant utilization rate at a low carbon-confined material dosage, therefore, the present invention has a significant advantage in the dosage of the agent, can reduce the degradation cost of organic pollutants, and promote the engineering application of the method.
[0033] 2. The present invention has experimentally confirmed that in the process of treating wastewater containing organic pollutants by the method of the present invention, the carbon-confined material activates peracetic acid to produce hydroxyl radicals, organic free radicals, singlet oxygen and Co (IV) to degrade the organic pollutants in the wastewater, and the carbon-confined material can achieve the continuous existence of active species under the confinement effect, thereby achieving the continuous degradation of organic pollutants by active species. Specifically, after 2 hours of reaction, the carbon-confined material / peracetic acid system can still detect the presence of active species through EPR, and the adduct peak area continues to increase; after running for 120 hours under continuous flow, it can still achieve a 70% degradation efficiency of naproxen; without adding peracetic acid and carbon-confined materials, this method can achieve complete degradation of naproxen in 3 rounds. The above factors are all conducive to effectively reducing the treatment cost of wastewater containing organic pollutants.
[0034] 3. The method of the present invention is mainly used in combination with biological treatment to improve the biodegradability of wastewater biological treatment while removing organic pollutants in wastewater. In the process of wastewater treatment, carbon-confined materials activate peracetic acid to produce organic matter such as acetic acid, which can provide a carbon source for the growth of microorganisms in the biological treatment stage. Therefore, when the method of the present invention is used in conjunction with biological treatment, the addition of carbon sources can be reduced, and the cost of adding carbon sources can be reduced. At the same time, the preparation method of the carbon-confined material of the present invention is simple, the conditions are mild, and it has a large cost advantage during preparation. In addition, the method of the present invention can achieve continuous activation of peracetic acid and continuous generation of advanced oxidation species under the condition of low carbon-confined material dosage, which is conducive to reducing the cost of adding agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Figures (a) and (b) are the SEM images and EDS-mapping images of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1, respectively.
[0036] Figure 2 Figures (a) and (b) are TEM and HRTEM images of Co@CoO-P123 prepared in Example 1. Figure 2 Figures (c) and (d) are the TEM and HRTEM images of Co@CoO-F127 prepared in Example 1.
[0037] Figure 3 Figures (a) and (b) are BET diagrams of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 3 Figure (c) is the XRD spectra of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 3 Figure (d) is the FTIR spectra of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1.
[0038] Figure 4 Figure (a) is the full XPS spectrum of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 4 Figure (b) is the Tafel curves of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1, as well as the control Co and control CoO.
[0039] Figure 5 Figures (a) and (b) are the Raman spectra of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1, respectively.
[0040] Figure 6Figure (a) shows the variation of [NAP] / [NAP]0 with treatment time when NAP is degraded in Example 3. Figure 5 Figure (b) is the C / C0 test result of degrading different pollutants in Example 4. Figure 5 Figure (c) shows the change of [NAP] / [NAP]0 with treatment time when degrading different concentrations of NAP in Example 5. Figure 5 Figure (d) shows the change of [SMX] / [SMX]0 with treatment time when Example 6 degrades SMX in actual water.
[0041] Figure 7 Figure (a) shows the variation of the reaction rate constant of NAP degradation with the dosage of PAA in Example 7. Figure 7 Figure (b) shows the change of the reaction rate constant of NAP degradation in Example 8 with the addition amount of Co@CoO-P123.
[0042] Figure 8 This is the consumption of PAA in Example 7.
[0043] Fig. 9 Figures (a) and (b) are the sustainability test results of the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system during PAA activation and the stability test results during continuous flow operation in Examples 8 to 9.
[0044] Fig.10 is the effect of different quenchers on NAP degradation.
[0045] Fig.11 Figures (a) and (b) are the adduct signal peaks of DMPO-OH in Co@CoO-P123 / PAA system and Co@CoO-F127 / PAA system; Fig. 9 Figures (c) and (d) are the TEMPO signal peaks of Co@CoO-P123 / PAA system and Co@CoO-F127 / PAA system.
[0046] Fig.12 Figures (A) and (B) show the degradation of benzoic acid and the generation of 7-hydroxycoumarin using benzoic acid and coumarin as hydroxyl probes.
[0047] Fig.13 Figures (A) and (B) show the consumption of PMSO and the generation of PMSO2.
[0048] Fig.14 This is the generation of TEMPO-RO when TEMPO is used as a probe. DETAILED DESCRIPTION
[0049] The following examples further illustrate the method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosages provided by the present invention. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The technical personnel in the relevant field make some non-essential improvements and adjustments to the present invention according to the above invention content for specific implementation, which still belongs to the scope of protection of the present invention.
[0050] Example 1
[0051] In this embodiment, a carbon confined material, specifically a nitrogen-doped confined Co@CoO core-shell material, is prepared by the following steps:
[0052] (1) Add dopamine hydrochloride and block copolymer to an ethanol-water solution to make the concentration of dopamine hydrochloride and block copolymer in the ethanol-water solution 5 g / L and 10 g / L, and perform ultrasonic treatment until each component is fully dissolved to obtain block copolymer-dopamine hydrochloride micelles. Add cobalt nitrate hexahydrate to the block copolymer-dopamine hydrochloride micelles to a concentration of 2 mmol / L, stir and mix evenly, then quickly add 1,3,5-trimethylbenzene and ammonia water in sequence at a speed of 500 rpm / min, continue stirring for 30 minutes, adjust the speed to 300 rpm / min, continue stirring for 3 hours, centrifuge the obtained mixed solution, wash the obtained solid particles with ethanol and deionized water for multiple times, collect the solid particles and dry them.
[0053] In this step, the ethanol-water solution is prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 2:3, and 1,3,5-trimethylbenzene and ammonia water are added in a ratio of 0.9:100 and 1.5:100 to the volume ratio of 1,3,5-trimethylbenzene and ammonia water to the ethanol-water solution. In this step, two groups of experiments were conducted, the block copolymer used in the first group of experiments was Pluronic F127, and the block copolymer used in the second group of experiments was P123.
[0054] (2) The dried solid particles were heated to 350°C at a heating rate of 2°C / min in a N2 atmosphere, kept at this temperature for 3 hours, and then heated to 800°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, to obtain a nitrogen-doped confined Co@CoO core-shell material. When the block copolymer used is P123, the prepared nitrogen-doped confined Co@CoO core-shell material is referred to as Co@CoO-P123, or Co-P123 for short; when the block copolymer used is Pluronic F127, the prepared nitrogen-doped confined Co@CoO core-shell material is referred to as Co@CoO-F127, or CoO-F127 for short.
[0055] Example 2
[0056] In this example, the nitrogen-doped confined Co@CoO core-shell material prepared in Example 1 was characterized.
[0057] The nitrogen-doped confined Co@CoO core-shell material prepared in Example 1 was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), elemental distribution (EDS), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FT-IR), Raman spectroscopy (Raman) and electrochemical workstation.
[0058] Figure 1 Figures (a) and (b) are the SEM images and EDS-mapping images of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1, respectively. Figure 2 Figures (a) and (b) are TEM and HRTEM images of Co@CoO-P123 prepared in Example 1. Figure 2 Figures (c) and (d) are the TEM and HRTEM images of Co@CoO-F127 prepared in Example 1. Figure 3 Figures (a) and (b) are BET diagrams of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 3 Figure (c) is the XRD spectra of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 3 (d) is the FTIR spectra of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 4 Figure (a) is the full XPS spectrum of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1. Figure 4 Figure (b) is the Tafel curves of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1, as well as the control Co and control CoO. Figure 5 Figures (a) and (b) are the Raman spectra of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1, respectively.
[0059] Figure 1 The SEM results show that both Co@CoO-P123 and Co@CoO-F127 are granular with no significant difference in surface morphology and particle size of about 10-20 nm. Figure 1 The EDS results show that the four elements C, Co, N and O are uniformly distributed in Co@CoO-P123 and Co@CoO-F127.
[0060] Depend on Figure 2From the TEM images, it can be seen that for Co@CoO-P123 and Co@CoO-F127, the metal particles are completely wrapped in the carbon layer, forming a confined core-shell structure with metal particles as the core and nitrogen-doped carbon layer as the shell. According to the crystal plane theory, the relationship between the corresponding degree of 2θ in XRD and the corresponding crystal plane and crystal plane spacing can be analyzed. The surface crystal plane spacings of Co@CoO-P123 and Co@CoO-F127 were detected to be 0.25nm, 0.22nm and 0.32nm, corresponding to the CoO (1 1 1) crystal plane, Co (11 1) crystal plane and graphite carbon (0 0 2) crystal plane, respectively.
[0061] Depend on Figure 3 As shown in Figures (a) and (b), Co@CoO-P123 and Co@CoO-F127 are both typical mesoporous materials with a pore size of about 5 nm. Compared with Co@CoO-P123, Co@CoO-F127 has a larger specific surface area (381.0406 m 2 / g). By Figure 3 Figure (c) shows that the positions of the diffraction peaks of Co@CoO-P123 and Co@CoO-F127 are consistent with those of CoO (PDF#78-0431) and Co (PDF#15-0806). The characteristic diffraction peaks at 2θ=42.632°, 49.673°, 72.828°, 88.226°, 93.276°, 51.830°, 60.623° and 91.083° correspond to the (1 1 1), (2 0 0), (2 2 0), (31 1) and (2 2 2) crystal planes of CoO and the (1 1 1), (2 0 0) and (2 2 0) crystal planes of Co, respectively. Figure 3 As shown in Figure (d), the functional groups contained in Co@CoO-P123 and Co@CoO-F127 include CH, CO, C=NC and NH, etc. Since the hydrophilic segment of F127 is longer than that of P123, the vibration of the CH bond and NH bond of Co@CoO-F127 is stronger than that of Co@CoO-P123.
[0062] Depend on Figure 4 As shown in Figure (a), Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 mainly contain four elements: C, O, N, and Co. The nitrogen contents of the two are 1.05wt% and 1.71wt%, respectively. Figure 4As can be seen from Figure (b), the corrosion potential of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 is higher than that of Co and CoO alone, indicating that the electron transfer ability of Co@CoO-P123 and Co@CoO-F127 is stronger than that of Co and CoO, which can be attributed to the electronic interaction between Co and CoO in Co@CoO-P123 and Co@CoO-F127.
[0063] Depend on Figure 5 It can be seen that the Raman spectra of Co@CoO-P123 and Co@CoO-F127 are at 1580 cm -1 and 1350cm -1 The graphitized carbon peak and disordered carbon peak appear at the Co@CoO-P123 and Co@CoO-F127. D / I G The values are 1.85 and 0.98, respectively, indicating that Co@CoO-P123 has a higher degree of defects.
[0064] Through inductively coupled plasma emission spectroscopy (ICP) testing, it was found that the Co contents in Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 were 22.4wt% and 18.6wt%, respectively, indicating that a higher amount of metal loading can be achieved through the method of the present invention.
[0065] Example 3
[0066] In this example, the ability of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 to activate PAA to degrade the pollutant naproxen (NAP) was investigated.
[0067] (1) NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. PAA and carbon-confined materials (Co@CoO-P123 or Co@CoO-F127) were added to the simulated wastewater. The simulated wastewater was treated for 10 min under stirring conditions at 25±1°C. The pH value of the simulated wastewater was controlled to be 6.3, the amount of PAA added to the simulated wastewater was controlled to be 0.2 mmol / L, and the amount of carbon-confined materials added to the simulated wastewater was controlled to be 0.015 g / L.
[0068] During the simulated wastewater treatment process, samples were taken at regular intervals and filtered through a filter membrane. Sodium thiosulfate was added to terminate the reaction, and then the concentration of NAP [NAP] was determined by liquid chromatography (HPLC). The initial concentration of NAP was recorded as [NAP]0, and the change of [NAP] / [NAP]0 with the treatment time was calculated, and the reaction rate constant was calculated. The results are shown in Figure 6 The data for the Co-P123 and Co-F127 groups are shown in Figure (a).
[0069] (2) Determine the Co leached from the sample taken in step (1) by atomic absorption spectroscopy 2+ concentration, and then the corresponding concentration (leached Co 2+ The concentration of Co 2+ To activate PAA to degrade NAP, the operation is the same as step (1), except that the carbon confinement material in step (1) is replaced by the above concentration of Co 2+ .
[0070] During the simulated wastewater treatment process, samples were taken at regular intervals and filtered through a 0.22 μm filter membrane. Sodium thiosulfate was added to terminate the reaction, and then the NAP concentration [NAP] was determined by HPLC. The initial NAP concentration was recorded as [NAP]0, and the change of [NAP] / [NAP]0 with treatment time was calculated. The results are shown in the figure. Figure 6 (a) Learning Co 2+ Group data shown.
[0071] Depend on Figure 6 As shown in Figure (a), the leached Co 2+ Almost no contribution to the degradation of NAP, Co@CoO-P123 and Co@CoO-F127 activated PAA can achieve 100% degradation of NAP within 10 min, and the corresponding reaction rate constant k obs They are 0.5738 and 0.3218 respectively.
[0072] Example 4
[0073] In this example, the ability of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 to activate PAA to degrade different organic pollutants was investigated.
[0074] Phenol (PE), bisphenol A (BPA), sulfamethoxazole (SMX), sulfamethoxazole (SMZ), 4-chlorophenol (4-CP) and ampicillin (AMP) were prepared into solutions with a concentration of 10 μmol / L using deionized water as simulated wastewater.
[0075] PAA and carbon-confined materials (Co@CoO-P123 or Co@CoO-F127) were added to each simulated wastewater, and the simulated wastewater was treated for 10 minutes under stirring conditions at 25±1°C. The pH value of the simulated wastewater was controlled to be 6.3, the amount of PAA added to the simulated wastewater was controlled to be 0.2mmol / L, and the amount of carbon-confined materials added to the simulated wastewater was controlled to be 0.015g / L. After the simulated wastewater treatment was completed, the sample was filtered with a filter membrane, sodium thiosulfate was added to terminate the reaction, and then the concentration C of the pollutant was determined by HPLC. The initial concentration of the pollutant was recorded as C0, and C / C0 was calculated. The results are as follows: Figure 6 As shown in Figure (b).
[0076] Depend on Figure 6 As shown in Figure (b), Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 activated PAA to achieve the degradation of PE, BPA, SMX, SMZ, 4-CP and AMP, especially the degradation of SMX, SMZ and AMP. This shows that Co@CoO-P123 and Co@CoO-F127 have good degradation performance for a variety of micropollutants and have a wide range of applicability.
[0077] Example 5
[0078] In this example, the effect of NAP concentration on the activation of PAA and degradation of NAP by Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 was investigated.
[0079] NAP was prepared into solutions with concentrations of 10, 25, and 50 μmol / L using deionized water as simulated wastewater. PAA and carbon-confined materials (Co@CoO-P123 or Co@CoO-F127) were added to each simulated wastewater, and the simulated wastewater was treated for 10 minutes under stirring conditions at 25±1°C. The pH value of the simulated wastewater was controlled to be 6.3, the amount of PAA added to the simulated wastewater was controlled to be 0.2 mmol / L, and the amount of carbon-confined materials added to the simulated wastewater was controlled to be 0.015 g / L. During the treatment of simulated wastewater, samples were taken at regular intervals and filtered using a filter membrane. Sodium thiosulfate was added to terminate the reaction, and then the NAP concentration [NAP] was determined by HPLC. The initial concentration of NAP was recorded as [NAP]0, and the change of [NAP] / [NAP]0 with treatment time was calculated. The change of [NAP] / [NAP]0 with treatment time is shown in Figure 6 As shown in Figure (c).
[0080] Depend on Figure 6As shown in Figure (c), when the NAP concentration increases from 10 μmol / L to 50 μmol / L, the reaction rate decreases to a certain extent. However, after extending the reaction time, both Co@CoO-P123 and Co@CoO-F127 can activate PAA to achieve 100% removal of high-concentration NAP. This is mainly due to the fact that the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system can continuously produce a variety of active species.
[0081] Example 6
[0082] In this example, the ability of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 to activate PAA to degrade pollutants in actual water bodies was investigated.
[0083] Using the secondary effluent of the sewage treatment plant as a solvent, sulfamethoxazole (SMX) was prepared into a solution with a concentration of 10 μmol / L, and the solution was used as the wastewater to be treated. PAA and carbon-confined materials (Co@CoO-P123 or Co@CoO-F127) were added to the wastewater to be treated, and the wastewater was treated for 10 minutes under stirring conditions at 25±1°C. The amount of PAA added to the simulated wastewater was controlled to be 0.2 mmol / L, and the amount of carbon-confined materials added to the wastewater was controlled to be 0.015 g / L. During the wastewater treatment process, samples were taken at regular intervals and filtered with a filter membrane, and sodium thiosulfate was added to terminate the reaction. The concentration of SMX was then determined by HPLC and recorded as [SMX]. The initial concentration of SMX was recorded as [SMX]0, and [SMX] / [SMX] was calculated. 0。 The variation of [SMX] / [SMX]0 with processing time is shown in Figure 6 As shown in Figure (d).
[0084] Depend on Figure 6 As can be seen from Figure (d), the degradation efficiency of the pollutant SMX in the secondary effluent was not affected. Both the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system could achieve 100% degradation of SMX in the secondary effluent within 5 minutes, indicating that the Co@CoO-P123 and Co@CoO-F127 activated PAA degradation system for micropollutants has good resistance to environmental interference and has good application potential in actual complex water matrices.
[0085] Example 7
[0086] In this example, the effect of PAA concentration on the activation of PAA by Co@CoO-P123 prepared in Example 1 to degrade NAP was investigated.
[0087] NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. PAA and Co@CoO-P123 were added to the simulated wastewater, and the simulated wastewater was treated for 10 min under stirring conditions at 25±1°C, the pH value of the simulated wastewater was controlled to be 6.3, and the amount of carbon-confined material added to the simulated wastewater was controlled to be 0.015 g / L. In this embodiment, a total of 4 groups of experiments were conducted, and the concentration of PAA in each group of experiments was different, and other conditions were the same. The concentration of PAA in the simulated wastewater was controlled to be 50, 100, 200, and 400 μmol / L in each group of experiments.
[0088] During the simulated wastewater treatment process, samples were taken at regular intervals and filtered through a membrane. Sodium thiosulfate was added to terminate the reaction. The NAP concentration was then determined using HPLC and the reaction rate constant was calculated. The results are shown in Table 1. Figure 7 As shown in Figure (a).
[0089] Depend on Figure 7 As shown in Figure (a), when other experimental conditions remain unchanged, with the increase of PAA concentration, the removal rate of NAP also increases, but with the further increase of PAA concentration, the removal rate of NAP decreases. When the concentration of PAA in the simulated wastewater is 50, 100, 200, and 400 μmol / L, the reaction rate constants are 0.2082, 0.3507, 0.5739, and 0.4981 min, respectively. -1 Taking into account the pollutant removal rate and wastewater treatment cost, when the catalyst dosage in the wastewater is about 0.015 g / L, the PAA dosage in the wastewater is feasible between 50 and 400 μmol / L.
[0090] Example 8
[0091] In this example, the effect of the dosage of Co@CoO-P123 on the activation of PAA by Co@CoO-P123 to degrade NAP was investigated.
[0092] NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. PAA and Co@CoO-P123 were added to the simulated wastewater, and the simulated wastewater was treated for 10 min under stirring conditions at 25±1°C, the pH value of the simulated wastewater was controlled to be 6.3, and the concentration of PAA in the simulated wastewater was controlled to be 200 μmol / L. In this embodiment, a total of 5 groups of experiments were conducted, and the dosage of Co@CoO-P123 in each group of experiments was different, and other conditions were the same. The addition amount of Co@CoO-P123 in the simulated wastewater was controlled to be 0.005, 0.01, 0.015, 0.2, and 0.3 g / L in each group of experiments.
[0093] During the simulated wastewater treatment process, samples were taken at regular intervals and filtered through a membrane. Sodium thiosulfate was added to terminate the reaction. The NAP concentration was then determined by HPLC and the reaction rate constant was calculated. The results are shown in the figure. Figure 7 As shown in the bar graph in Figure (b), Figure 7 The curve in Figure (b) refers to the adsorption rate of NAP at different Co@CoO-P123 dosages (without adding PAA).
[0094] Depend on Figure 7 As can be seen from Figure (b), when other experimental conditions remain unchanged, with the increase of Co@CoO-P123 dosage, the removal rate of NAP also increases, but with the further increase of Co@CoO-P123 dosage, the adsorption rate of NAP also increases. Considering the pollutant removal rate and wastewater treatment cost, when the dosage of PAA in the wastewater is about 200 μmol / L, the dosage of Co@CoO-P123 in the wastewater is feasible between 0.005 and 0.3 g / L.
[0095] Example 9
[0096] In this example, the consumption of PAA when Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 are used to activate PAA. Methyl p-tolyl sulfide (MTS) is used as an indicator of residual PAA. The oxidation product generated by the reaction of MTS and PAA is sulfoxide MTSO. The consumption of PAA in the system can be tracked by detecting the concentration of MTSO through HPLC.
[0097] PAA and carbon-confined material (Co@CoO-P123 or Co@CoO-F127) were added to deionized water and reacted for 10 minutes under stirring conditions at 25±1°C. The amount of PAA added to the simulated wastewater was controlled to be 0.2mmol / L, and the amount of carbon-confined material added to the deionized water was controlled to be 0.015g / L. 500μL of samples were taken at 0min, 1min, 3min, 5min, 8min and 10min of reaction, filtered with a filter membrane, and immediately mixed with 250μL of 2.0mmol / L MTS solution prepared in advance with acetonitrile, and then the concentration of MTSO was determined by HPLC. Since the reaction coefficient of PAA and MTS is 1:1, the concentration of the generated MTSO is used to represent the concentration of PAA consumed. The results are shown in Figure 8 shown.
[0098] At 10 min, the concentrations of MTSO generated in the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system were 98.12 μmol / L and 87.78 μmol / L, respectively. That is, the amount of PAA consumed by the two systems was only 98.12 μmol / L and 87.78 μmol / L, indicating that the two systems have a high utilization efficiency of PAA when degrading pollutants.
[0099] Example 10
[0100] In this example, the durability of Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 in activating PAA to degrade NAP was investigated.
[0101] NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. In the first reaction, PAA and carbon-confined material (Co@CoO-P123 or Co@CoO-F127) were first added to the simulated wastewater. The simulated wastewater was treated for 15 min under stirring conditions at 25±1°C. The pH value of the simulated wastewater was controlled to 6.3, the amount of PAA added to the simulated wastewater was controlled to 0.2 mmol / L, and the amount of carbon-confined material added to the simulated wastewater was controlled to 0.015 g / L.
[0102] After the first reaction, a newly prepared NAP solution was directly added to the wastewater to make the NAP concentration in the wastewater 10 μmol / L, and the second reaction was started without the additional addition of PAA and carbon-confined materials. Similarly, after the second reaction, a newly prepared concentrated NAP solution was directly added to the wastewater to make the NAP concentration of the wastewater 10 μmol / L to start the third reaction. This cycle of reactions was repeated 4 to 5 times.
[0103] During the whole process of simulated wastewater treatment, samples were taken at regular intervals and filtered through a membrane. Sodium thiosulfate was added to terminate the reaction, and then the NAP concentration [NAP] was determined by HPLC. The initial concentration of NAP was recorded as [NAP]0, and the change of [NAP] / [NAP]0 with the treatment time was calculated. The results are shown in Fig. 9 As shown in Figure (a).
[0104] Depend on Fig. 9As shown in Figure (a), after the first reaction, the Co@CoO-P123 / PAA system can achieve complete degradation of the second added NAP without adding additional oxidant PAA and carbon-confined materials, and achieve efficient degradation of the third added NAP, with a removal rate of more than 80% for the third added NAP; after the first reaction, the Co@CoO-F127 / PAA system can achieve complete degradation of the second added NAP without adding additional oxidant PAA and carbon-confined materials, and achieve efficient degradation of the third added NAP, with a removal rate of more than 90% for the third added NAP, and a removal rate of about 50% for the fourth added NAP. The above experimental results show that both the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system can achieve continuous generation and existence of active species for a long time, thereby achieving continuous degradation of pollutants.
[0105] Embodiment 11
[0106] In this example, the stability of PAA degradation of NAP by Co@CoO-P123 and Co@CoO-F127 prepared in Example 1 was investigated. Specifically, a continuous flow system was used to evaluate the stability of the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system in degrading pollutants over a long period of time.
[0107] NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water, and PAA was added to the NAP solution until the concentration of PAA was 0.2 mmol / L to form a NAP / PAA mixed solution. 50 mg of carbon-confined material (Co@CoO-P123 or Co@CoO-F127) was fixed in the reaction column using cotton as a carrier, and hoses were connected to the inlet and outlet of the reaction column respectively. The NAP / PAA mixed solution was continuously passed into the reaction column from the inlet by a peristaltic pump at a flow rate of 0.8 to 1.5 mL / min, and then continuously discharged into the water outlet container from the outlet, thereby forming a continuous flow system for wastewater treatment. During the operation of the continuous flow system, samples were taken at the outlet at regular intervals and filtered with a filter membrane. Sodium thiosulfate was added to terminate the reaction, and then the NAP concentration C was determined by HPLC. The initial concentration of NAP was recorded as C0, and the change of C / C0 with treatment time was calculated. The results are shown in the figure. Fig. 9 (b) as shown.
[0108] Depend on Fig. 9As shown in (b), the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system can completely remove NAP within the first 60 hours during the operation of the continuous flow system. After the continuous flow system has been running for 120 hours, the removal rate of NAP by the two catalytic systems can still reach more than 60%. This shows that the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system can achieve long-term stable operation in the continuous flow system, further confirming that the carbon confined material described in the present invention has the characteristics of high efficiency, stability and sustainability, and has the potential for practical application.
[0109] Example 12
[0110] In this example, various experiments were performed to investigate the types and reaction pathways of active oxidative species generated by the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system when degrading NAP in wastewater.
[0111] 1. Quenching experiment
[0112] The quenchers used include methanol (MeOH), 2,4-hexadiene (2,4-HD), tert-butyl alcohol (TBA) and dimethyl sulfoxide (DMSO). MeOH and 2,4-HD can quench both hydroxyl (·OH) and organic free radicals (RO·), TBA can only quench ·OH, and DMSO can quench singlet oxygen ( 1 O2).
[0113] NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. PAA and the carbon-confined material (Co@CoO-P123 or Co@CoO-F127) prepared in Example 1 were added to the simulated wastewater, and the simulated wastewater was treated for 10 min under stirring conditions at 25±1°C, the pH value of the simulated wastewater was controlled to be 6.3, the amount of PAA added to the simulated wastewater was controlled to be 0.2 mmol / L, and the amount of carbon-confined material added to the simulated wastewater was controlled to be 0.015 g / L. Different concentrations and different types of quenchers were added to the simulated wastewater before the reaction started, as follows:
[0114] Control group: no quencher was added;
[0115] MeOH group: MeOH was added to the simulated wastewater until the concentration of MeOH was 100 mmol / L;
[0116] TBA group: TBA was added to the simulated wastewater until the concentration of TBA was 100 mmol / L;
[0117] 2,4-HD group: 2,4-HD was added to the simulated wastewater until the concentration of 2,4-HD reached 5mmol / L;
[0118] DMSO group: DMSO was added to the simulated wastewater until the concentration of DMSO reached 10 mmol / L;
[0119] In the process of simulated wastewater treatment, samples were taken at 0min, 1min, 3min, 5min, 8min and 10min of wastewater treatment, filtered with a filter membrane, and sodium thiosulfate was added to terminate the reaction. Then, HPLC was used to determine the NAP concentration and the reaction rate constant k was calculated. obs .
[0120] After adding the corresponding quencher, the higher the degree of inhibition on the degradation of pollutants, the greater the contribution of the active species quenched by the corresponding quencher to the degradation of pollutants (excluding the solvent effect and the consumption of PAA itself by the quencher). Fig.10 As shown in the figure, when 100mmol / L TBA is added, the degradation of NAP by the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system is slightly inhibited, especially the Co@CoO-F127 / PAA system, indicating that the contribution of ·OH in the two catalytic systems is relatively weak. When 100mmol / L MeOH and 5mmol / L 2,4-HD are added, the degree of inhibition of the degradation of NAP by the two systems is significantly higher than that of the experimental group with TBA added, indicating that RO· in both systems plays a role in the degradation of NAP. At the same time, the addition of DMSO greatly inhibits the degradation of NAP by the two systems, indicating that the degradation of NAP by the two systems is significantly inhibited. 1 O2 also has an important contribution to the degradation process of NAP. The quenching experimental results show that ·OH, RO· and 1 O2, these active species.
[0121] 2. Electron paramagnetic resonance (EPR) detection
[0122] By combining with a spin trap, EPR can capture the characteristic peaks formed by free radicals and the trap, thereby qualitatively determining different active species. When 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) is used as a trap, EPR can capture the adduct signal peak of DMPO-OH with a peak shape of 1:2:2:1, thereby determining the presence of ·OH; when 2,2,6,6-tetramethylpiperidine (TEMP) is used as a trap, if there is 1 In the presence of O2, tetramethylpiperidinyl oxide (TEMPO) can be generated, and a 1:1:1 triplet peak can be detected by EPR.
[0123] A capture agent (DMPO or TEMP) was added to a sampling tube containing 2 mL of deionized water to a concentration of 100 mmol / L. PAA and the carbon confined material (Co@CoO-P123 or Co@CoO-F127) prepared in Example 1 were then added to start the reaction. During the reaction, samples were drawn with a capillary at regular intervals and detected by EPR. The concentration of PAA in water was controlled to be 1 mmol / L, and the amount of carbon confined material added to water was controlled to be 0.075 g / L. The test results are shown in FIG. Fig.11 shown.
[0124] like Fig.11 As shown in Figures (a) and (b), the 1:2:2:1 DMPO-OH adduct signal peak was detected in both the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system during the reaction, and the signal peak showed a trend of continuous enhancement with the extension of the reaction time. This enhancement trend lasted for 90 to 120 minutes, indicating that ·OH was formed in both systems. At the same time, the ·OH signal peak of the Co@CoO-P123 / PAA system was stronger than that of the Co@CoO-F127 / PAA system. The experimental results show that the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system have continuous ·OH generation and existence for a long time during the reaction, which may be the reason for inducing the continuous degradation of NAP in Example 11. In addition, compared with the Co@CoO-P123 / PAA system, the Co@CoO-F127 / PAA system produces less ·OH, which is consistent with the inhibition result of TBA in the above quenching experiment. like Fig.11 As shown in Figures (c) and (d), a strong 1:1:1 signal peak was detected in both the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system, and the signal also increased with the extension of the reaction time, indicating that there is 1 The continuous generation and presence of O2.
[0125] 3. Probe Experiment
[0126] Benzoic acid (BA) can selectively react with ·OH to be degraded, and coumarin can react with ·OH to generate 7-hydroxycoumarin. Therefore, the generation of ·OH in the system can be investigated by detecting the BA residue and the generation of 7-hydroxycoumarin by HPLC after the reaction of BA and coumarin with ·OH. High-valent metals can react with methyl phenyl sulfoxide (PMSO) to generate methyl phenyl sulfone (PMSO2) through double electron transfer, so the conversion of PMSO to PMSO2 in the system can be detected to determine whether Co(IV) is generated in the system.
[0127] (1) OH probe experiment
[0128] BA and coumarin were prepared into 10 μmol / L and 2 mmol / L solutions respectively with deionized water as probes. PAA and the carbon-confined material (Co@CoO-P123 or Co@CoO-F127) prepared in Example 1 were added to the probe solution, and the reaction was carried out for 120 min under stirring conditions. The amount of PAA added to the probe solution was controlled to be 0.2 mmol / L, and the amount of carbon-confined material added to the probe solution was controlled to be 15 mg / L. During the probe experiment, samples were taken at regular intervals and filtered through a filter membrane, and Na2S2O3 was added to quench the reaction. The concentrations of BA and 7-hydroxycoumarin were detected by HPLC, and the results are shown as follows. Fig.12 As shown in Figures (A) and (B).
[0129] Depend on Fig.12 It can be seen that during the 2h reaction process, BA showed a trend of continuous degradation, and the concentration of 7-hydroxycoumarin showed a trend of continuous increase. The two experimental results jointly showed that during the reaction process of Co@CoO-P123 / PAA system and Co@CoO-F127 / PAA system, ·OH had a trend of continuous generation, which further confirmed the conclusion of EPR detection.
[0130] (2) Co(IV) probe experiment
[0131] PMSO was prepared into a 250 μmol / L solution with deionized water as a probe. PAA and the carbon-confined material (Co@CoO-P123 or Co@CoO-F127) prepared in Example 1 were added to the probe solution and reacted for 120 min under stirring conditions. The amount of PAA added to the probe solution was 0.2 mmol / L, and the amount of carbon-confined material added to the probe solution was controlled to be 15 mg / L. During the probe experiment, samples were taken at regular intervals and filtered through a filter membrane, Na2S2O3 was added to quench the reaction, and the residual concentration of PMSO and the generated concentration of PMSO2 were detected by HPLC. The results are shown in Figure 2. Fig.13 As shown in Figures (A) and (B).
[0132] Depend on Fig.13 It can be seen that during the reaction, PMSO in the Co@CoO-P123 / PAA system and the Co@CoO-F127 / PAA system showed a trend of continuous consumption. At the same time, PMSO2 also showed a trend of continuous generation, and the sum of PMSO and PMSO2 almost tended to be stable. In addition, the conversion rate of PMSO-PMSO2 was close to 100%. The experimental results showed that Co(IV) existed in both systems, and Co(IV) was mainly generated continuously within the first 60 minutes of the reaction.
[0133] (3)RO probe
[0134] 2,2,6,6-Tetramethylpiperidinyl-N-oxyl radical (TEMPO) can capture RO·(CH3COO· or CH3·) to generate relatively stable CH3COO·-TEMPO or CH3·-TEMPO. The adducts can be detected by high performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-QTOF-MS / MS) to further illustrate the formation of RO· in the system.
[0135] TEMPO was prepared into a 5 mmol / L solution with deionized water as a probe. PAA and the carbon confined material (Co@CoO-P123 or Co@CoO-F127) prepared in Example 1 were added to the probe solution and reacted for 10 min under stirring conditions. The amount of PAA added to the probe solution was controlled to be 0.2 mmol / L, and the amount of carbon confined material added to the probe solution was controlled to be 15 mg / L. After the reaction was completed, samples were taken and detected using UPLC-QTOF-MS / MS. The results are as follows Fig.14 shown.
[0136] Depend on Fig.14 It can be seen that in the Co@CoO-P123 / PAA system, CH3·-TEMPO and CH3COO·-TEMPO adduct signal peaks with m / z of 172.1696 and 216.1594 were detected, indicating that CH3· and CH3COO· were generated in the system. In the Co@CoO-F127 / PAA system, the CH3COO·-TEMPO adduct signal peak with m / z of 216.1594 was detected, indicating that CH3COO· was generated in the system.
[0137] Embodiment 13
[0138] In this embodiment, a carbon confined material (nitrogen-doped confined Co@CoO core-shell material) was prepared and activated with PAA to degrade NAP, and the steps were as follows:
[0139] (1) Add dopamine hydrochloride and block copolymer to an ethanol-water solution to make the concentration of dopamine hydrochloride and block copolymer in the ethanol-water solution 8 g / L and 12 g / L, perform ultrasonic treatment until each component is fully dissolved, and obtain block copolymer-dopamine hydrochloride micelles. Add cobalt nitrate hexahydrate to the block copolymer-dopamine hydrochloride micelles to a concentration of 4 mmol / L, stir and mix evenly, then quickly add 1,3,5-trimethylbenzene and ammonia water in sequence at a speed of 500 rpm / min, continue stirring for 60 minutes, adjust the speed to 300 rpm / min, continue stirring for 4 hours, centrifuge the obtained mixed solution, wash the obtained solid particles with ethanol and deionized water for multiple times, collect the solid particles and dry them.
[0140] In this step, the ethanol-water solution is prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 2:3, and 1,3,5-trimethylbenzene and ammonia water are added in a ratio of 1.2:100 and 2:100 to the volume ratio of 1,3,5-trimethylbenzene and ammonia water to the ethanol-water solution. The block copolymer used is Pluronic F108. F124
[0141] (2) The dried solid particles were heated to 360°C at a heating rate of 2°C / min under N2 atmosphere and kept at this temperature for 2 h. Then, the temperature was increased to 900°C at a heating rate of 2°C / min and kept at this temperature for 1 h to obtain a nitrogen-doped confined Co@CoO core-shell material, which was recorded as Co@CoO-F108.
[0142] (3) NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. PAA and Co@CoO-F108 were added to the simulated wastewater. The simulated wastewater was treated for 10 min under stirring conditions at 25±1°C. The pH value of the simulated wastewater was controlled to be 6.3, the amount of PAA added to the simulated wastewater was controlled to be 0.2 mmol / L, and the amount of Co@CoO-F108 added to the simulated wastewater was controlled to be 0.02 g / L.
[0143] During the treatment of simulated wastewater, samples were taken at regular intervals and filtered through a membrane. Sodium thiosulfate was added to terminate the reaction. Subsequently, HPLC was used to determine the concentration of NAP and the removal rate of NAP was calculated, and the result was 100%.
[0144] Embodiment 14
[0145] In this embodiment, a carbon confined material (nitrogen-doped confined Co@CoO core-shell material) was prepared and activated with PAA to degrade NAP, and the steps were as follows:
[0146] (1) Add dopamine hydrochloride and block copolymer to an ethanol-water solution to make the concentration of dopamine hydrochloride and block copolymer in the ethanol-water solution 4 g / L and 12 g / L, and perform ultrasonic treatment until each component is fully dissolved to obtain block copolymer-dopamine hydrochloride micelles. Add cobalt nitrate hexahydrate to the block copolymer-dopamine hydrochloride micelles to a concentration of 3 mmol / L, stir and mix evenly, then quickly add 1,3,5-trimethylbenzene and ammonia water in sequence at a speed of 500 rpm / min, continue stirring for 30 minutes, adjust the speed to 300 rpm / min, continue stirring for 2.5 hours, centrifuge the obtained mixed solution, wash the obtained solid particles with ethanol and deionized water for multiple times, collect the solid particles and dry them.
[0147] In this step, the ethanol-water solution is prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 2:3, and 1,3,5-trimethylbenzene and ammonia water are added in a ratio of 1:100 and 1:100 to the volume ratio of 1,3,5-trimethylbenzene and ammonia water to the ethanol-water solution. The block copolymer used is F124.
[0148] (2) The dried solid particles were heated to 340°C at a heating rate of 2°C / min under N2 atmosphere and kept at this temperature for 4 h. Then, the temperature was increased to 800°C at a heating rate of 2°C / min and kept at this temperature for 3 h to obtain a nitrogen-doped confined Co@CoO core-shell material, which was recorded as Co@CoO-F124.
[0149] (3) NAP was prepared into a solution with a concentration of 10 μmol / L using deionized water as simulated wastewater. PAA and Co@CoO-F124 were added to the simulated wastewater. The simulated wastewater was treated for 8 min under stirring conditions at 25±1°C. The pH value of the simulated wastewater was controlled to 6.3, the amount of PAA added to the simulated wastewater was controlled to 0.3 mmol / L, and the amount of Co@CoO-F124 added to the simulated wastewater was controlled to 0.025 g / L.
[0150] During the treatment of simulated wastewater, samples were taken at regular intervals and filtered through a membrane. Sodium thiosulfate was added to terminate the reaction. Subsequently, HPLC was used to determine the concentration of NAP and the removal rate of NAP was calculated, and the result was 100%.
Claims
1. A method for achieving continuous degradation of pollutants at low dosage based on self-assembly induced carbon confined materials, characterized in that: The following steps are involved: Adding peracetic acid and a carbon-confined material to wastewater containing organic pollutants, treating the wastewater under stirring conditions, wherein during the wastewater treatment process, the carbon-confined material activates the peracetic acid to generate hydroxyl radicals, organic free radicals, singlet oxygen and Co(IV) to degrade the organic pollutants in the wastewater; The carbon confined material is composed of a cobalt material and a nitrogen-doped carbon material coating the cobalt material, the cobalt material is composed of Co and CoO, and the carbon confined material is a nanoparticle with a core-shell structure.
2. According to claim 1, the method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage is characterized in that: The cobalt content in the carbon confined material is 18 wt% to 23 wt%, and the nitrogen content is 1.0 wt% to 2.4 wt%.
3. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to claim 1, characterized in that: In the nitrogen-doped carbon material, the carbon phase composition is graphitized carbon and disordered carbon, and the intensity ratio of the D band to the G band in the Raman spectrum of the nitrogen-doped carbon material is 0.98-1.
85.
4. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to claim 1, characterized in that: The particle size of the carbon confined material is 10-20 nm, and the carbon confined material has a mesoporous structure with an average pore size not exceeding 10 nm.
5. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to any one of claims 1 to 4, characterized in that: The preparation method of the carbon confined material is as follows: (1) adding dopamine hydrochloride and a block copolymer to an ethanol-water solution, ultrasonically treating to form block copolymer-dopamine hydrochloride micelles, adding a water-soluble cobalt salt to the block copolymer-dopamine hydrochloride micelles, mixing thoroughly, adding 1,3,5-trimethylbenzene and ammonia water, stirring to react for 3 to 5 hours, separating the solid and the liquid, and washing the solid phase; In this step, dopamine hydrochloride is added to the ethanol-water solution at a mass ratio of 1:(1.5-3) to the block copolymer, the concentration of dopamine hydrochloride in the ethanol-water solution is controlled to be 4-8 g / L, the concentration of the water-soluble cobalt salt in the block copolymer-dopamine hydrochloride micelle is controlled to be 2-4 mmol / L, and 1,3,5-trimethylbenzene and ammonia water are added at a volume ratio of (0.9-1.2):100 and (1-2):100 to the ethanol-water solution; the volume content of ethanol in the ethanol-water solution is 50%-60%; (2) The solid phase obtained in step (1) is heated to 340-360° C. in a N2 atmosphere and kept at this temperature for 2-4 hours, and then heated to 800-900° C. and kept at this temperature for 1-3 hours.
6. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to claim 5, characterized in that: The block copolymer is polyethylene oxide-block-polypropylene oxide-block-polyethylene oxide, or polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol.
7. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to any one of claims 1 to 4, characterized in that: The dosage of peracetic acid in the wastewater is controlled to be 50-400 μmol / L.
8. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to any one of claims 1 to 4, characterized in that: The dosage of the carbon confinement material in the wastewater is controlled to be 5-50 mg / L.
9. The method for achieving continuous degradation of pollutants based on self-assembly induced carbon confined materials at low dosage according to any one of claims 1 to 4, characterized in that: Control the wastewater treatment time to 10 to 120 minutes.
Citation Information
Patent Citations
BE652248A
Nitrogen-doped carbon material supported by cobalt nitride and preparation method thereof
CN110038614A
Method for degrading organic pollutants in water by activating peracetic acid with nitrogen-doped carbon material
CN111606405A
Preparation method and application of Co@CoO / NCNT core-shell adsorbent
CN111672454A
Method for treating wastewater by synergistically activating peracetic acid through zero-valent iron-cobalt bimetallic material
CN113461225A
Cited By
Cobalt-loaded peanut shell biochar / peracetic acid water treatment synergistic system and application thereof
CN121571147A
Surface co / coo heterojunction modified nitrogen-doped carbon-coated copper oxide photocatalyst, preparation method and application thereof
CN122682625A